RELAWAN PAJAK 2023: MENDORONG KEPATUHAN WAJIB PAJAK MELALUI PENDAMPINGAN PELAPORAN SPT TAHUNAN DAN PEMADANAN NIK-NPWP - Aliya Tiara Fatiha; Rahma Aulia Safriza; Khy'sh Nusri Leapatra Chamalinda (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Tax is the primary source of state revenue that finances national development. One of the factors that can determine the amount of state revenue is the level of taxpayers’ compliance. The service aims to increase taxpayer compliance by tax volunteers. It is hoped that the presence of tax volunteers at KPP Pratama Bangkalan will play a role in increasing taxpayers’ compliance through service to taxpayers by helping taxpayers in Bangkalan Regency to report their annual tax reporting and support the implementation of matching NIK into NPWP. Tax volunteers are also tasked with providing socialization, education, and information related to annual tax reporting using e-filling. The service program is carried out for approximately five months using the Community-Based Participatory Research (CBPR) method with stages starting from the pre-training, training, implementation, and evaluation. The results of this activity are based on data from KPP Pratama Bangkalan as of 2 Feb – 31 March 2023, there are 35,709 Annual Tax Reporting for Individual Taxpayers that have been reported on time. The evaluation results show that the majority of taxpayers are satisfied with the services provided by tax volunteers.  ---  Pajak merupakan sumber utama pendapatan negara yang mendanai pembangunan nasional. Salah satu faktor yang menentukan jumlah penerimaan negara adalah tingkat kepatuhan wajib pajak. Pengabdian ini dilakukan dengan tujuan untuk mendorong kepatuhan wajib pajak melalui program relawan pajak. Diharapkan dengan hadirnya relawan pajak di KPP Pratama Bangkalan berperan dalam mendorong kepatuhan pajak melalui pelayanan kepada wajib pajak dalam hal pelaporan SPT Tahunan dan mendukung implementasi pemadanan NIK-NPWP. Relawan pajak juga bertugas memberikan sosialisasi, edukasi, dan informasi yang berkaitan dengan pelaporan SPT Tahunan dengan menggunakan e-filling. Program pengabdian dilakukan melalui metode Community Based Participatory Research (CBPR), dengan tahapan yang dimulai dari tahap pra pelatihan, pelatihan, pelaksanaan, dan evaluasi. Hasil kegiatan pengabdian ini berdasarkan data dari KPP Pratama Bangkalan per 2 Feb – 31 Maret 2023 terdapat 35.709 SPT Tahunan Wajib Pajak Orang Pribadi yang telah dilaporkan secara tepat waktu. Hasil evaluasi menunjukkan bahwa wajib pajak merasa puas atas pelayanan asistensi yang diberikan relawan pajak.